Performance improvement of zinc oxide photoanode-based dye-sensitized solar cells by multi-walled carbon nanotube - Chindaduang, Anon; Duangkaew, Pattasuda; Pratontep, Sirapat; Tumcharern, Gamoiwan (My University, 2010)
Unique electrical and surface-to-volume properties of carbon nanotubes have made these conductive molecules highly attractive in many applications. In this work, the influence of multi-walled carbon nanotubes into a zinc oxide active layer of dye-sensitized zinc oxide solar cell has been investigated. With this method, a significant improvement in the performance of the solar cell has been achieved. Compared to the typical zinc oxide photoelectrochemical cells, the photocurrent- voltage characteristics of the fabricated cell containing 0.05 percent by weight of carbon nanotubes in the metal oxide film displayed a higher short-circuit photocurrent, consequently caused an increase of the solar-to-electricity conversion efficiency by a factor of approximately 1.4. Further increase of the conductive carbon material resulted in a decrease of the energy conversion of the photovoltaic cell. The enhancement of the energy conversion at this optimum carbon nanotube loading may be attributed to the dye-adsorption ability and the electrochemical activity of the composite photoanodes. The fabricated photovoltaic cells with the highest efficiency exhibited the maximum dye adsorption intensity and the minimum charge transfer resistance, as measured by ultraviolet-visible spectroscopy and electrochemical impedance spectroscopy, respectively . Copyright © 2010 American Scientific Publishers.
Keywords: Carbon nanotubes; Dye-sensitized solar cells; Zinc oxide